A bizarre Jurassic maniraptoran theropod with preserved evidence of membranous wings - Xu, Xing; Zheng, Xiaoting; Sullivan, Corwin; Wang, Xiaoli; Xing, Lida; Wang, Yan; Zhang, Xiaomei; O’Connor, Jingmai K.; Zhang, Fucheng; Pan, Yanhong (Nature (London), 2015)
A recently discovered fossil belonging to the Scansoriopterygidae, a group of bizarre dinosaurs closely related to birds, represents a new scansoriopterygid species and preserves evidence of a membranous aerodynamic surface very different from a classic avian wing. Taking flight by the wrist At the base of the dinosaur lineage that eventually led to birds there is a small group of bizarre dinosaurs called scansoriopterygids. They were very small, often with long digits and are usually reconstructed as tree-dwelling lemur-like creatures. Here Xing Xu and colleagues present what is possibly the strangest scansoriopterygid so far discovered. Named Yi qi , the tiny animal, from 160 million-year-old sediments in China, has an unusual assortment of stiff filamentous feathers and also two long bony elements attached to the wrists, unlike anything seen previously in any dinosaur. These structures, resembling extraneous bones seen in a variety of tetrapods, may have supported a membrane that might have sustained gliding flight. Traces of such a membrane are preserved with the specimen. The wings of birds and their closest theropod relatives share a uniform fundamental architecture, with pinnate flight feathers as the key component 1 , 2 , 3 . Here we report a new scansoriopterygid theropod, Yi qi gen. et sp. nov., based on a new specimen from the Middle–Upper Jurassic period Tiaojishan Formation of Hebei Province, China 4 . Yi is nested phylogenetically among winged theropods but has large stiff filamentous feathers of an unusual type on both the forelimb and hindlimb. However, the filamentous feathers of Yi resemble pinnate feathers in bearing morphologically diverse melanosomes 5 . Most surprisingly, Yi has a long rod-like bone extending from each wrist, and patches of membranous tissue preserved between the rod-like bones and the manual digits. Analogous features are unknown in any dinosaur but occur in various flying and gliding tetrapods 6 , 7 , 8 , 9 , 10 , suggesting the intriguing possibility that Yi had membranous aerodynamic surfaces totally different from the archetypal feathered wings of birds and their closest relatives. Documentation of the unique forelimbs of Yi greatly increases the morphological disparity known to exist among dinosaurs, and highlights the extraordinary breadth and richness of the evolutionary experimentation that took place close to the origin of birds.